A study Malaysian university students' perspectives on the essence of a meaningful life - Ahmad Azmi AbdelHamid Esmaeil; Ismail Maakip; Wirawati Ngui Yi Xe; Murnizam Halik (ResearchGate, 2024)
In this qualitative study, we examine Malaysian university student’s views on the essence of life’s meaning. Through interpretive phenomenological analysis of interviews with 15 students, we uncover that a meaningful life, as perceived by them, is rooted in the pursuit of personal purpose, experiencing positive emotions and nurturing enriching relationships. Students stress the importance of existential mattering, evidencedby altruistic action and societal contributions. Personal qrowth stands out as well, particularly self-improvement and spiritual development, with an emphasis on faith. This study enhances our understanding of how student conceptualize meaning in life, delineating the multifaceted aspects that contribute to their sense of fulfillment and well-being.The insghts derived offer significant implications for designing educational and psychological interventions that aim to boost students’ life satisfaction and enrich their understanding of what constitutes life’s meaning.